Mitigating anxiety in english public speaking: implications and interventions - Johari, Aiza; Morni, Affidah; Nik Fauzi, Sheela Faizura; Sahari, Siti Huzaimah; Sarkawi, Adib (GADING Journal for the Social Sciences, 2025)
The ability of students to communicate effectively in the target language is essential, as it demonstrates their capacity to express clear ideas and thoughts. Delivering a presentation in English is a challenging task that requires control of both verbal and non-verbal aspects, including precise vocabulary usage, grammatical accuracy, clear pronunciation, proper intonation, and effective body language. Therefore, speaking English in public often creates fear and anxiety among students, especially when they are learners of English as Foreign Language (EFL). In an EFL context, the learners generally use English for specific purposes like academic studies, travel, or international communication, rather than for everyday interaction. Most of them felt apprehensive to speak English in front of the audience, therefore, they had a negative perception of their mind which affects their performances. This study explores the common issue of public speaking anxiety (PSA) among EFL learners, particularly in the context of English Public Speaking. It assesses the impact of this anxiety on their presentation skills and identifies strategies to improve public speaking abilities, as well as to reduce their anxiety and fear. Utilizing a quantitative research approach, data was collected through adapted questionnaires, distributed to 40 international students from three South East Asia countries. These respondents took part in various English communication activities, including oral presentations and public speaking. In addition, an observation took place in the controlled setting designed to stimulate a typical public speaking environment. The findings reveal that public speaking anxiety is prevalent among them, primarily due to cultural barriers and limited opportunities for skill development. This study underscores the communication challenges faced by these populations and offers practical solutions to improve their oral communication skills. These findings contribute to the understanding of English Public Speaking among EFL learners and offer valuable recommendations for enhancing English oral presentation and communication skills. The insights obtained are also crucial for developing educational programs and workshops that cater to improve English Public Speaking and boost the speakers’ confidence levels.